Mathematical Model of HBV/HCV Co-Infection - Shah, Nita H; Sheoran, Nisha; Jayswal, Ekta (Discontinuity, Nonlinearity, and Complexity, 2026)
The co-infection of hepatitis B (HBV) and hepatitis C (HCV) virus is a complex clinical entity that has an estimated worldwide prevalence of 1--15%. In this paper HBV/HCV co-infection is modelled mathematically through the set of deterministic non-linear differential equations. This dynamical system has four equilibrium points i.e. disease-free, co-infection free, HCV free and endemic point. Reproduction number is computed for endemic equilibria. Local stability for all the equilibrium point is proved using Routh-Hurwitz criterion. Global stability is also studied for all the equilibria. The sensitivity analysis of relevant parameters in reproduction number is analyzed to see the effect of each parameter in disease spread.